Efektivitas Bilas Rebusan Daun Sirih Merah (Piper Crocatum) dan Kompres Lidah Buaya (Aloe Vera) untuk Penyembuhan Luka Perineum Derajat II di Puskesmas Cikajang Kabupaten Garut Tahun 2024 - Maryamah, Aam (STIKes Budi Mulia Sriwijaya, 2024)
Various complications can be experienced by mothers in the postpartum period, one of which is postpartum infection caused by improper perineal wound care. Based on the Cikajang public health center report in September-October 2023, there were 76 postpartum women and as many as 32 people (42%) who experienced grade II perineal wounds, while there were 3 cases of perineal wound infection. Efforts to heal perineal wounds can be overcome pharmacologically and non-pharmacologically using herbal ingredients such as red betel leaf and aloe vera. Betel leaf and aloe vera contain chemical compounds that function as antibiotics and anti-bacteria that can help the wound healing process. The purpose of the study was to determine the effectiveness of red betel leaf decoction rinse (Piper Crocatum) and aloe vera compress (Aloe vera) for healing second degree perineal wounds at the Cikajang Public health center, Garut District in 2024. The research method used was qualitative research with a case study approach by comparing two postpartum women who experienced grade II perineal wounds. One was given the intervention of red betel leaf decoction rinse and aloe vera compress, the other was given the intervention of dry clean technique and observed with the REEDA scale. The results of the study respondents who were given the intervention of red betel leaf decoction rinse and aloe vera compress had a faster healing value compared to the respondents who were given a dry clean technique. Conclusion Red betel leaf decoction rinse and aloe vera compress are effective in accelerating the healing of grade II perineal wounds. Suggestions for health workers can implement interventions to rinse red betel leaf decoction and aloe vera compresses to accelerate perineal wound healing in postpartum mothers and can increase further knowledge.